Uji Kinerja Prototipe Vacuum Dryer untuk Minyak Merah Kelapa Sawit - Ellys Mei Sundari; Winda Apriani; Suhendra; Feby Nopriandy (Jurnal Engine: Energi, Manufaktur, dan Material, 2026)
One of the main challenges in processing red palm oil (RPO) was maintaining the stability of active compounds during the drying process. Therefore, appropriate technology was needed to maintain the nutritional quality of red oil. This study aims to evaluate the performance of a laboratory-scale vacuum dryer specifically designed for drying red palm oil. Vacuum drying technology was chosen because it operates at low temperatures and low pressures, thereby minimizing thermal damage to sensitive compounds. Tests were conducted to determine the relationship between temperature changes RPO and the percentage of mass loss of the material against heating time. The heating time was varied to 30, 45, and 60 minutes. Based on the test results, heating time significantly affects the increase in temperature and the decrease in RPO mass. The rise in RPO temperature occurs most rapidly during the first 15 minutes; after that, the RPO temperature remains relatively stable. The results of the mass loss test showed a mass loss of 95.40% at 30 minutes, 94.20% at 45 minutes, and 94.00% at 60 minutes.